The Story of the Naval Arctic Research Laboratory - Reed, John C. (ARCTIC, 1969)
The Laboratory, established in Aug 1947 by the US Office of Naval Research, itself not yet two years old, was started by seven men led by the first director, L. Irving at Barrow, Alaska at the main supply camp of the Naval Petroleum Reserve No.4, where exploration continued until 1953. The Arctic Institute and later the Univ of Alaska have been closely associated with the ARL. The key people in ONR and successive directors of the Lab are noted, the main interests and directions sketched. Some 1500 persons representing 86 universities in nine countries and many institutions have participated in research at the Laboratory; many US government agencies have used it as a project base.